ANALISIS PENGAMBILAN KEPUTUSAN NASABAH PEMBIAYAAN MURABAHAH PADA BMT DAARUT TAUHIID BANDUNG - Asep Suryanto; Adah Sa’adah (Universitas Siliwangi, 2019)
The objective of this research was to find out what factors underlie Daarut Tauhiid BMTcustomers in applying of murabaha financing. The research method used is descriptive research method with a qualitative approach. The data sources in this study involve primary data sources and secondary data sources. Primary data sources, namely the unit head, account officer, and members of Daarut Tauhiid BMT as murabaha financing customers at the BMT. Secondary data sources involve modules, documents at Daarut Tauhiid BMT relating to the topic of research. The data analysis techniques are through the stages of data reduction, data display and data verification. The results of the research show that the factors that could underlie customer decisions in applying The results showed that the factors underlying the customer's decision in applying of murabaha financing at Daarut Tauhiid Baitul mal wa Tamwil (BMT) were images of the Daarut Tauhiid environment, reference groups, customer needs in certain situations, supporting personal work, customer perceptions of syariah compliance